Sex differences in the relationship between pain and autonomic outflow during a cold pressor test - Laila A. Chaudhry; Yasmine Coovadia; Brittany K. Schwende; Danielle E. Berbrier; Will Huckins; Jinan Saboune; Derek A. Skolnik; Emily K. Van Berkel; Jeffrey S. Mogil; Charlotte W. Usselman (Biology of Sex Differences)
Abstract Background Chronic pain is partly maintained by the sympathetic nervous system, whose activity is best measured by muscle sympathetic nerve activity (MSNA). MSNA responses to acute pain have been thoroughly investigated, whereas MSNA responses to longer-lasting pain are poorly understood. Therefore, this study examined the relationship between pain ratings and peroneal MSNA during a tonic cold pressor test (CPT) in male and female participants. Methods We obtained MSNA measures during a 6 min CPT in 18 young adult (20–33 years) men and women. Verbal pain ratings (0–10) and autonomic outcomes (heart rate [HR], mean arterial blood pressure [MAP], and MSNA) were assessed simultaneously at multiple time points across the CPT. Results Pain, HR, and MAP increased in the initial 30s in both sexes. Females increased their MSNA burst frequency (BF) to a greater extent than males. Across the full CPT we observed a positive relationship between pain and HR in males, a positive relationship between pain and MSNA BF in females, and a negative relationship between pain and MSNA burst amplitude in females. Conclusions Overall, males displayed a strong relationship between tonic pain and HR, an index of parasympathetic activity, whereas females displayed strong and offsetting relationships between tonic pain and purely sympathetic MSNA variables. These observations suggest sex differences in autonomic mechanisms during tonic pain, which may have relevance to ongoing efforts to modulate pain via manipulations of the autonomic nervous system, as well as sex/gender disparities in chronic pain prevalence.